The titanium PV I endosteal implant from beta-titanium alloy Ti 38Nb 6Ta - Prachar, Patrik; Bartakova, Sonia; Vanek, Jiri (Biomedical papers, 2015)
Aim: The aim of this study was to use the beta-titanium alloy Ti38Nb6Ta for production of a new construction line of implants, perform testing on animals and preclinical tests. Materials and Methods: Within this study, a new PV I implant with five construction variants was developed. The implant includes three types of threads - microthreads and flat threads of two types with a different depth. Further, the PV I implant was tested on minipigs. Subsequently, preclinical tests of 150 implants were performed and assessed. The age interval of patients was from 18 to 74 years. Results: Beta titanium alloy exhibited higher strength than titanium alloys. Anti-corrosion resistance was also higher. The implant from beta-alloy was inserted in the tibias of minipigs. Sections showed good osseointegration of the PV I implant. During the preclinical tests, 150 implants were inserted with the success rate of 99.33% after the two year assessment. The assessment also included handicapped patients who are not usually assessed in classical studies. Finally, the implantation protocol and documentation of a new implantation system PV I was designed. At the same time the industrial sample of this implant was formed and accepted. Conclusion: A new anti-rotation PV I implant with microthreads and conical anchorage of the abutment into the fixture was formed. The beta-titanium alloy Ti38Nb6Ta used for the implant was biocompatible and had higher mechanical and physical properties than the existing titanium alloys. The PV I implant was recommended for clinical application.
Keywords: beta-titanium alloy; anti-rotation feature; microthreads; handicapped patient